Yahoo Web Search

  1. Express V( t ) in the form R cos ( t +a) 3 cos t - 2 sin t = R cos ( t +a) = R... sin t sin a 3 cos t = R cos t cos a 3 = R cos a 2 sin t = R sin t sin a 2 = R sin a R^2 (sin^2 a + cos^2 a) = 2...

    2 Answers · Science & Mathematics · 04/04/2007

  2. Given: t = 2*pi * (sqrt(L) + 1)/((g*(L- t ))) ( t * (g*(L- t ...3 +2gt*pi))) / gt Therefore: L = ((pi + sqrt((pi^2 - g* t ^3 + 2*g* t *pi))) / g* t )^2 or L = ((pi - sqrt((pi^2 - g* t ^3 + 2...

    2 Answers · Science & Mathematics · 24/08/2008

  3. Square both sides. 4 cos^2 t = 1 + 2 sin t + sin^2 t cos^2 t = 1 - sin^2 t Substituting this into the...2 t 5 sin^2 t + 2 sin t - 3 = 0 This is a quadratic equation in sin t . Using the quadratic formula, we get sin t = {- 2 + or - sqrt [4 - 4 * 5 * (- 3...

    3 Answers · Science & Mathematics · 22/11/2016

  4. g( t ) = t ^2 - 2t + 3/ t + 2 ; g( t ) = 6 Please use enough parentheses to be...either g( t ) = t² - 2t + (3/ t ) + 2 or g( t ) = t² - 2t + 3/( t + 2). Case 1: g( t ) = 6 = t² - 2t + (3/ t ) + 2. ...

    1 Answers · Science & Mathematics · 29/03/2010

  5. Since r( t ) = <-2 sin t , -2 sin t , -5 cos t >, we have by differentiation: r'( t ) = <-2 cos t , -2 cos t , 5 sin t > r''( t ) = <2 sin t , 2 sin t , 5 cos t >...

    1 Answers · Science & Mathematics · 27/05/2013

  6. g’’( t ) = sin t + cos t So g'( t ) = -cos t + sin t + C Since g’(π) = -cos(π) + sin(π) + C = 1 + ...

    2 Answers · Science & Mathematics · 22/12/2007

  7. y = t ^(n) y' = n * t ^(n - 1) y'' = n * (n - 1) * t ^(n - 2) Subbing those in: [ t ^2] * n * (n - 1) * t ^(n...0 t ^(n) * ( n - 2 )^2 = 0 ( n - 2 )^2 = 0 ----> n = 2 y( t ) = A * t ^2 + B * t ^2 * ln( t ) we said...

    2 Answers · Science & Mathematics · 12/06/2012

  8. t = 7 First convert the 1/3 to a fraction with ( t +5) on the bottom and the other two terms to have a 3...5 24 = 4t - 4 24 + 4 = 4t - 4 + 4 28 = 4t 4t / 4 = 28 / 4 t = 7 PS: It checks back nicely: 8...

    3 Answers · Science & Mathematics · 25/04/2007

  9. You can t divide both sides by t because you have to consider that t might be equal to zero...divide by zero; so that would cause a problem. If you test 0 as a solution: 3· t = t² 3·(0) = (0)² 0 = 0 Indeed it is a solution...

    4 Answers · Science & Mathematics · 13/10/2008

  10. #1 f( t ) = t²∙cos(b∙ t ) The Laplace transform for cosine is well known and can be found in every transform table: ℒ{ cos(b∙ t ) } = s/(s² + b²) The factor t² corresponds...

    2 Answers · Science & Mathematics · 05/12/2012

  1. Try asking your question on Yahoo Answers